HUBUNGAN PERILAKU TERHADAP KEBERSIHAN GIGI DAN MULUT MURID-MURID SEKOLAH DASAR NEGERI (SDN) DKI JAKARTA PENDERITA GIGI BERJEJAL (Kajian pada murid-murid kelas 4-6 SDN di DKI Jakarta) - Tri Erri Atoeti; Isnani Jenie; Joko Kusnoto (Faculty of Dentistry, Universitas Indonesia, 2015)
Indonesian are having oral health disease which relate with oral hygiene. Most of oral health diseases are dental caries and periodontal disease. Dental crowding is one type of dental malocclusion that cause those diseases. On the other hand, behaviour has an important role to influence oral health status. The aim of this study to get information about the relation between behavior and oral hygiene of school children with dental crowding in DKI Jakarta. This study has been done on 277 fourth to sixth grade elementary school children from 5 districts at DKI Jakarta. This observational study has been done by chi-square test. The result has shown that there is no relation between behaviour to oral hygiene of dental crowding school children (p=0.93).